Peran Kecerdasan Emosional dan Suasana Hati (Mood) terhadap Kepuasan Kerja dan Stres Kerja di Badan Pengelolaan Keuangan Pendapatan dan Aset Daerah Kabupaten Bantul - Deandra Indah Kusuma Putri; Prayekti Prayekti; Didik Subiyanto (Universitas Batanghari Jambi, 2023)
One of the qualities and advantages of an area can be seen from the service to the community in that area. Regional community services can run well if the government and employees working in this field have the ability to manage the quality of human resources, especially in terms of controlling and controlling the emotions and moods of employees. This study aims to examine the level of the role of emotional intelligence and mood on job satisfaction and work stress that is often experienced by an employee. This research is a descriptive research by taking a sample of 83 samples taken by purposive sampling technique. The research findings show that emotional intelligence has a positive and significant effect on job satisfaction but does not have a significant effect on job stress. Meanwhile, mood has a positive and insignificant effect on job satisfaction, but has a significant effect on work stress. Other research findings reveal that emotional intelligence and mood have a role in job satisfaction and job stress.